Nurses’ Adherence to Patient Safety Principles: A Systematic Review - Mojtaba Vaismoradi; Susanna Tella; Patricia A. Logan; Jayden Khakurel; Flores Vizcaya-Moreno (Switzerland, 2025)
Background: Quality-of-care improvement and prevention of practice errors is dependent on nurses’ adherence to the principles of patient safety. Aims: This paper aims to provide a systematic review of the international literature, to synthesise knowledge and explore factors that influence nurses’ adherence to patient-safety principles. Methods: Electronic databases in English, Norwegian, and Finnish languages were searched, using appropriate keywords to retrieve empirical articles published from 2010–2019. Using the theoretical domains of the Vincent’s framework for analysing risk and safety in clinical practice, we synthesized our findings according to ‘patient’, ‘healthcare provider’, ‘task’, ‘work environment’, and ‘organisation and management’. Findings: Six articles were found that focused on adherence to patient-safety principles during clinical nursing interventions. They focused on the management of peripheral venous catheters, surgical hand rubbing instructions, double-checking policies of medicines management, nursing handover between wards, cardiac monitoring and surveillance, and care-associated infection precautions.Patients’ participation, healthcare providers’ knowledge and attitudes, collaboration by nurses, appropriate equipment and electronic systems, education and regular feedback, and standardization of the care process influenced nurses’ adherence to patient-safety principles. Conclusions: The revelation of individual and systemic factors has implications for nursing care practice, as both influence adherence to patient-safety principles. More studies using qualitative and quantitative methods are required to enhance our knowledge of measures needed to improve nurse’ adherence to patient-safety principles and their effects on patient-safety outcomes.